The hippocampus in clinical neuroscience: 5 tables - Szabo, Kristina; Hennerici, Michael G. (The hippocampus in clinical neuroscience, 2014)
The hippocampus is one of the most intriguing structures of the human brain. Damage to this part causes symptoms ranging from transient disorders accompanied by tiny lesions to severely debilitating cognitive disorders with marked tissue loss. This publication provides a predominantly clinical approach to the complex workings of the hippocampus from different perspectives, ranging from basic principles to specific diseases. The first part of the book summarizes current knowledge regarding the structure and physiology of the hippocampus and establishes the ties to basic neuroscience. The second part deals with the function and assessment of the human hippocampus, including memory function, neuropsychological measures, and conventional and functional imaging studies. The chapters of the third part are devoted to the hippocampus in neurological disorders, e.g. the interaction between stress and memory function, and the pathological conditions of common as well as selected rare neurological diseases affecting the hippocampus. The book is highly recommended to clinical neurologists who wish to gain a broad understanding of this complex and fascinating organ in terms of basic principles, modern imaging findings, and specific diseases.
A broad overview of this complex and fascinating organ